Sentiment Analysis Towards Leading Tourism in Banyuwangi As A Policy Consideration to Improve Economic Stability and Resilience - Darmanto Darmanto; Diego Irsandy; Zaki Abiyu Aqilah; Rismania Hartanti Putri Yulianing Damayanti (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2025)
The tourism sector is one of the important aspects in improving the economy of a region, including Banyuwangi. The Banyuwangi Regency Government took steps to make tourism a leading sector in supporting the economy. Efforts to increase economic stability and resilience can be made by optimizing tourism, which includes tourist destinations, restaurants and inns. Utilizing social media to analyze tourist reviews is a strategy in optimizing tourism. The purpose of this research is to analyze the sentiment of tourists in Banyuwangi. Sentiment analysis approach with Lexicon-based method analyzed with Support Vector Machine algorithm is done to find out the opinion of tourists about tourist sites in Banyuwangi. The analysis results show that the SVM algorithm can provide a fairly good performance with an accuracy of more than 70%. Based on sentiment analysis, improving the online reservation system and regular training for staff will reduce visitor dissatisfaction regarding waiting time and service quality. In addition, maintaining natural beauty and aesthetics through environmental conservation programs can increase Banyuwangi’s tourism attractiveness and support the hospitality, restaurant and transportation sectors. The government can implement policies that are more responsive to the needs and desires of tourists, thereby increasing visitor satisfaction and strengthening the competitiveness of the tourism sector.